EFFECTIVENESS OF DEEP LEARNING BASED ON PROBLEM-BASED LEARNING ON STUDENTS' CRITICAL THINKING IN BRAIN ROT CONTEXT - Talenta Valentina Christi; Ramlah Ramlah; Indra Budiman (EMTEKA: Jurnal Pendidikan Matematika, 2026)
Mathematical critical thinking skills are essential competencies in mathematics education, yet their development among students remains suboptimal. This condition is compounded by the brain rot phenomenon arising from excessive digital content consumption and the dominance of conventional teaching practices that offer limited opportunities for deep cognitive engagement. This study aimed to analyze differences in the improvement of mathematical critical thinking skills between students taught through Deep Learning-oriented instruction using the Problem Based Learning (PBL) model and those taught through Teacher-Centered Learning (TCL) using the Direct Instruction model, while also describing students' critical thinking profiles based on gadget-use intensity categories. A quasi-experimental method with a Nonequivalent Pretest–Posttest Control Group Design was employed. Participants comprised 92 tenth-grade students from SMA Negeri 2 Cileungsi, with 45 students in the experimental class and 47 in the control class, selected through purposive sampling. Data were collected via essay tests measuring mathematical critical thinking skills and questionnaires assessing gadget-use intensity. Analysis was conducted using the Shapiro–Wilk normality test, Levene's homogeneity test, and an independent samples t-test. Results indicated a significant difference in the improvement of mathematical critical thinking skills between groups (t = −7.715; p = 0.000 < 0.05), favoring the PBL class. Additionally, students with high gadget-use intensity recorded lower mean pretest scores (47.73) compared to moderate (56.08) and low (64.52) intensity groups, suggesting that the brain rot phenomenon negatively impacts students' mathematical critical thinking skills.